Therapeutic Drug Monitoring of Second- and Third-Generation Antipsychotic Drugs-Influence of Smoking Behavior and Inflammation on Pharmacokinetics - Nicole Moschny; Gudrun Hefner; Renate Grohmann; Gabriel Eckermann; Hannah B Maier; Johanna Seifert; Johannes Heck; Flverly Francis; Stefan Bleich; Sermin Toto; Catharina Meissner (MDPI AG, 2021)
Both inflammation and smoking can influence a drug's pharmacokinetic properties, i.e., its liberation, absorption, distribution, metabolism, and elimination. Depending on, e.g., pharmacogenetics, these changes may alter treatment response or cause serious adverse drug reactions and are thus of clinical relevance. Antipsychotic drugs, used in the treatment of psychosis and schizophrenia, should be closely monitored due to multiple factors (e.g., the narrow therapeutic window of certain psychotropic drugs, the chronicity of most mental illnesses, and the common occurrence of polypharmacotherapy in psychiatry). Therapeutic drug monitoring (TDM) aids with drug titration by enabling the quantification of patients' drug levels. Recommendations on the use of TDM during treatment with psychotropic drugs are presented in the Consensus Guidelines for Therapeutic Drug Monitoring in Neuropsychopharmacology; however, data on antipsychotic drug levels during inflammation or after changes in smoking behavior-both clinically relevant in psychiatry-that can aid clinical decision making are sparse. The following narrative review provides an overview of relevant literature regarding TDM in psychiatry, particularly in the context of second- and third-generation antipsychotic drugs, inflammation, and smoking behavior. It aims to spread awareness regarding TDM (most pronouncedly of clozapine and olanzapine) as a tool to optimize drug safety and provide patient-tailored treatment.